physical culture: more than two hours of physical education. (Revista Electrónica REDINE, 2018)
Health worldwide is considered the main priority of all State policy, and that is why there are several studies that have been conducted by different researchers for years, to improve the physical and mental state of people. In this sense, it is recognized the importance for the body to maintain the physical and psychic balance, which allows the development of daily activities within an active society. However, in Venezuela and other Latin American countries, high levels of sedentary lifestyle are revealed, which in turn causes obesity, the development of diseases and even death. This article is an essay in which the concept of Physical Culture is presented as an alternative to diminish a sedentary lifestyle; also, it is argued about the reasons why this culture should be promoted in all educational levels, and especially in the university.